Comparison of the Effectiveness of Self-Repair Training and Acceptance and Commitment Training on Self-Acceptance and Affective Capital in Women with Symptoms of Borderline Personality Disorder - Yekta , Mohammadreza; Golparvar, Mohsen; Yousefi , Zahra (Iranian Journal of Neurodevelopmental Disorders, 2026)
Purpose: The present study was conducted with the aim of comparing the effectiveness of self-repair training and acceptance and commitment training on self-acceptance and affective capital in women with symptoms of borderline personality disorder. Methods and Materials: The study employed a quasi-experimental design with three phases: pretest, posttest, and follow-up, including a control group. The statistical population consisted of women with symptoms of borderline personality disorder in the city of Isfahan during the summer of 2025 who refer to four active centers in this field. From this population, 60 women were purposively selected and assigned to two experimental groups and one control group (20 participants in each group). The Self-Acceptance Questionnaire (Chamberlain & Haaga, 2001) and the Affective Capital Questionnaire (Golparvar, 2016) were used to measure the dependent variables across the three phases. The self-repair training group and the acceptance and commitment training group each received their respective interventions separately over 10 sessions, while the control group received no training. Data were analyzed using repeated measures analysis of variance and Bonferroni post hoc test via SPSS version 26. Findings: The results indicated that there were significant differences between the self-repair training group and the acceptance and commitment training group compared to the control group in terms of self-acceptance and affective capital (p < .05). However, no significant difference was observed between the two intervention groups regarding their effectiveness on self-acceptance and affective capital (p > .05). Conclusion: Based on the findings, both self-repair training and acceptance and commitment-based training can be utilized to enhance the levels of self-acceptance and affective capital in women with symptoms of borderline personality disorder.